Business Competition in the Era of Technology: Shifting the 4P to 4C - Lisa Kurniasari Wibisono; Isak Pasulu (Proceeding of The International Conference on Economics and Business, 2022)
Micro, small and medium enterprises (MSMEs) play a vital role in economic development and growth, especially in Indonesia. It is widely recognized that MSMEs are very important be-cause of their main characteristics that distinguish them from large enterprises, especially because MSMEs are labour-intensive enterprises, exist in all locations, especially in rural areas, are more dependent on local raw materials, and are the main providers of goods and services. Along with the development of the mindset of the community, the majority of MSME actors have also changed their mindset in determining the marketing strategy used, from product orientation, consumer orientation, value orientation, technology orientation and to build the super smart society. Business digitalization also evolve the marketing mix from 4P (product, place, price and promotion) to 4C (co-creation, currency, communal activation, and conversation). However, there are barriers in the face of digitalization economy, including technology adoption and cyber-crime.